Why activity based costing (ABC) is still tagging behind the traditional costing in Malaysia? - Devinaga Rasiah (Journal of Applied Finance & Banking, 2011)
This study compares activity-based costing (ABC) model and traditional costing method in Malaysia. Activity based costing (ABC) which was developed into the manufacturing/service sectors in Malaysia. It calculates the cost and performance of activities, resources and cost objects. It can be considered as an alternative model to Traditional Cost-based accounting systems. In this study the results indicated that most operations managers believed that their present cost systems were adequate for decision making. In certain circumstances, operations managers evaluated their cost systems as more effective than those using other cost systems. Activity-based costing systems were evaluated as somewhat more useful, but no relevant literature was found to indicate that either the external or internal environment of the firm was correlated with the choice of cost system.
Keywords: D24; D61; 330; activity-based costing; cost drivers; overheads; traditional costing